Pengaruh Influencer Endorsement dan Online Customer Reviews terhadap Purchase Intention melalui Customer Trust di TikTok Shop pada Produk MS Glow - Marchika Putri Agustin; Elia Resha Fatmawati; Guruh Taufan Hariyadi; Suhita Whini Setyahuni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Digital marketing strategies now play a major role in influencing consumer purchasing behavior. This study examines the extent to which online customer reviews and influencer support affect purchase intention among MS Glow customers who shop through TikTok Shop, using customer trust as a connecting construct. A survey instrument is used in the quantitative research design. Probability sampling was used to select 120 respondents, all of whom had to have bought MS Glow products on TikTok Shop and read product reviews on the same site. The data was processed using SmartPLS version 4.0 and partial least squares-structural equation modeling (PLS-SEM). The results show that influencer support and online customer reviews both favorably and significantly contribute to the development of consumer trust, while customer trust itself positively and significantly increases purchase intention. According to mediation testing, customer trust serves as a partial mediator in the relationship between online customer reviews and purchase intention, but it does not function as a connecting channel between influencer support and purchase intention. These findings underscore the importance of influencer endorsement, online customer reviews, and customer trust in enhancing purchase intention among us consumers of MS Glow products on TikTok Shop.